If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 16 = 106 Reorder the terms: 16 + 6x = 106 Solving 16 + 6x = 106 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 6x = 106 + -16 Combine like terms: 16 + -16 = 0 0 + 6x = 106 + -16 6x = 106 + -16 Combine like terms: 106 + -16 = 90 6x = 90 Divide each side by '6'. x = 15 Simplifying x = 15
| 4x^2+4y^2+6x+8y-5=0 | | 3*(x+12)+5x=92 | | 6x+16 = 106 | | 7.4x+17=76.2 | | -6x-8 = -50 | | 2.7x+18=63.9 | | 10x+17=177 | | -11x+17=-126 | | 2x-15 = -19 | | 25x+7=207 | | 3(2x-4)+8=6 | | 2x/3=(X-10)/4 | | 7w+14=14 | | 7w+14=4 | | 19-5x=-15 | | 11x+13=200 | | -5x+16=-54 | | 16m^2-81(m-3)(m-3)=0 | | 1+3x=-3+9x | | 3p+12=6p-24 | | 16=25 | | 5x-0.6x=7.48 | | 2.9=8.3x | | .5x=.4+.4x | | -6x+9x=-15 | | 12-3x=-8.7 | | 3.6(x+5)=50.4 | | w/4=w/2=1/4=W | | 2x^3+19x^2+38x-35=0 | | a+(a+3)+(a-5)=76 | | y+x=63 | | 5.1x-18=48.3 |